æ±‰è¯æˆè¯ä¸å››ç§åŠ¨ç‰©ï¼ˆç‹—ã€è›‡ã€é©¬ã€é¾™ï¼‰çš„å«ä¹‰åˆ†æž - Marini, Betty; Thamrin, Lily; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIdioms are an inseparable part of human life, and they are closely related to human language and culture. What humans see or experience through all aspects of life constitutes related idioms to express specific meanings, and the number of idioms is extremely rich. Chinese animal idioms are one of the parts of Chinese idioms. They are the imagery of animals to form the overall meaning of an idiom. This article takes Chinese idioms with animal morphemes (dog, snake, horse, dragon) as research objects. The reasons are mainly based on these two points: 1. Human beings have a close relationship with animals in their lives. 2. The use of animal idioms is frequent. This article uses the Chinese Idiom Learning Dictionary and the Xinhua Idiom Dictionary to collect the required "animal idioms" and analyze the meaning of related idioms to find out the meaning of the animal morphemes. Through the analysis method, the author summarizes the meanings of the morphemes of "dog, snake, horse and dragon.Keywords: Mandarin, Mandarin Animal Idiom, Meaning Analyse